Laparoscopic and open Burch colposuspension for stress urinary incontinence: Advantages / disadvantages - Ahmed Ali Obaid; Shiren Ali Al-Hamzawi; Ahmed Abdulameer Alwan (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
OBJECTIVE: Stress incontinence (SUI) causes a significant physical and psychological burden on women. Laparoscopic vaginal suspension (LC), used in the treatment of women with SUI, is known for its advantages such as smaller incisions, short hospital stay, and better aesthetic results. This article throws light upon the advantages and disadvantages of (LC) and opens up Burch vaginal (OC) incontinence along with its associated complications.PATIENTS AND METHODS: Between December 1, 2017 and February 10, 2019, 26 women with SUI with physical, social, and psychological consequences from two hospitals were enrolled in this study. The sample was divided into two equal groups of 13 women each. Data were collected and statistically analyzed. P ≤ 0.05 is statistically significant.Results: The study showed that the operational time was significantly shorter in the OC method compared to the LC approach (59.2 ± 5.3 min, 91 ± 4.5 min, respectively). Mean blood loss was higher in the OC approach than in the LC approach (152.2 ± 30.3, 143.3 ± 38.6), respectively. The LC approach has minimal pain and a shorter hospital stay compared to the OC approach. Patients with the LC approach required less analgesia (8.9 ± 1.3 mg vs 2.5 ± 1.8 mg) and less hospital stay (110.3 ± 11.4 hours vs 70.2 ± 8.9 hours) after surgery. Resumption of normal activity was faster in the LC approach (25.1 ± (12.6) days, 18.9 ± (12.5) days) than in the OC approach. There was no significant difference between the OK and LC approaches in terms of complications.Conclusion: Although LC is a superior and less invasive approach than the Open Burch approach in terms of hospital stay, blood loss, pain and recovery time, the operation time is longer.